Alternative Solutions to Environmental Health Issues: A Systematic Review - Guterres Magno, Nuno Pedro; Amaral Gaio, Frenania Ermelinda; Garcia, Graciela; Menezes da Silva, Ines da Cruz; Barreto Moniz, Aurizia Elisa (Syntax Literate, 2025)
Introduction: According to the World Health Organization (WHO), environmental health is an important component in ensuring the sustainability of human life and ecology. Environmental health encompasses all aspects of human health, including quality of life, and is determined by physical, chemical, biological, social, and psychological factors. Some environmental health issues include air pollution, irresponsible waste disposal, climate change, and environmental degradation. Situation analysis, problem identification, prioritization of issues, development of alternative problem-solving activities, and problem-solving actions are steps in the problem-solving process to improve health and minimize its detrimental impact on environmental health. Method: used for article analysis, synthesis, and academic sources discussing alternative approaches to solving environmental health problems, starting with identification using relevant academic data from articles accessed in databases such as Google Scholar, PubMed, and Scopus, approximately 60 articles accessed for the extraction stage, with inclusion and exclusion criteria for articles within the last 7 years. Results: The health and community services must work together effectively to ensure that programs and services run smoothly and have strong regulations and law enforcement to regulate and implement comprehensive public health care for environmental health. Additionally, it is crucial to enforce environmental health standards and protect the environment from hazardous activities that cause diseases. The Four Rs—reduce, reuse, and recycle—are one of the strategies that can be used to prevent disease by minimizing waste pollution for environmental health and its impact on human health. Conclusion One alternative approach to addressing environmental health issues is public health, which offers solutions based on cooperation and a comprehensive approach to ensure effective prevention through health programs that encompass both promotive and preventive measures. A more holistic approach and effective management also require an integrated approach that includes environmental waste management and community diagnosis principles and methods. Proceed-Precede to address environmental health issues with credible and systematic data. an effective strategy for understanding and addressing environmental health issues comprehensively, strengthening regulations and law enforcement is also necessary to ensure effective policies for a healthy environment. By working together, the government, private sector, and the general public can discuss priority programs and activities that harm environmental health, which can also reduce pollution, prevent diseases, and improve healthy living standards in a healthy environment.